The Association Between Sanitation, Hygiene, and Stunting in Children Under Two-Years (An Analysis of Indonesia’s Basic Health Research, 2013) - Badriyah, Lulu'ul; Syafiq, Ahmad (UI Scholars Hub, 2017)
Background: This study aims to identify the relationship between sanitation, hygiene, and stunting in children under two-years in Indonesia. Methods: This was a cross-sectional study that examined 9,688 children under the age of two. We obtained data from Indonesia's Basic Health Research paper that was released in 2013 and applied multiple logistic regression analysis. The prevalence of stunting amongst children under two-years in 2013 was 33.3%. Results: Our analysis showed that stunting is closely related to low birth weight, age, gender, exclusive breastfeeding, socioeconomic status, garbage removal, and waste management. Appropriate sanitation and hygiene had a significant impact on stunting amongst children under two-years in Indonesia, with waste management and low birth weight being the most important indicators. Conclusions: Nutrition, socioeconomic status, and a healthy environment are key to ensure children under two-years meet the recommended growth standards.